Overburden Damage Degree-Based Optimization of High-Intensity Mining Parameters and Engineering Practices in China’s Western Mining Area - Xiang He; Cun Zhang; Penghua Han (Geofluids)
China’s western mining area is an arid and semiarid area with a fragile ecological environment, and the high-intensity mining activities aggravate ecological damage. Reasonable choice of the mining parameters (i.e., mining height, panel width, and advancing speed) can not only improve the mining efficiency but also weaken the mining-induced deformation and failures of the overburden and surface. The statistical analysis of the relationship between the mining parameters and periodic weighting interval (PWI) proves that mining parameters have significant influence on overburden failure. In this study, the damage constitutive equation was derived, and the overburden damage degree was defined to quantitatively characterize mining-induced stratum damage in a three-dimensional space. FLAC3D numerical models embedded with a damage constitutive equation were built to compare the panel width effect and advancing speed effect between the overburden damage degree and the water-conducted fracture zone (WCFZ). The reasonable range for mining parameters of the panel 12401 was provided based on the fitting function of the overburden damage degree versus mining parameters. The field measurements were carried out on panel 12401 of the Shangwan coal mine, including the advancing speed, PWI, and ground crack development. The results show that, under constant engineering and geological conditions, the damage degree of overburden will be weakened by increasing the advancing speed, reducing the mining height, or shortening the panel width. The overburden damage degree is more accurate than the height of the water-conducted fractured zone. The reasonable mining parameters of the panel 12401 are 8.8 m in mining height, 300 m in panel width, and 13.47 to 20.58 m/d in advancing speed, respectively. The field measurement results of the PWI and ground cracks have verified the validity using the overburden damage degree to determine high-intensity mining parameters.